Analysis of the Volume of Excavation and Stockpiling in the Bicycle Path Development Works jl. RE. Martadinata Batam Using the Elevation Difference Method with Contractor Calculations - Yustika Irawati Simbolon; Ade Jaya Saputra (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2023)
In eartgworks there are othe sub-works including ordinary excavation work, ordinary embankment from excavated sources, selected embankment from excavated sources, preparation of bicycle lane bodies, and cones. In this final project the author tries to make a comprasion of the volume of excavation and embankment. The outhor uses the AutoCAD Software application to a calculate the area, pours the result of the area calculation into Microsoft Excel to calculate the volume of excavations and embankments and uses the AutoCAD application to visualize excavations and embankments. Based on the result of research concudated by the author, the authors conclude that there is a significant difference in volume result from those obtained by the author using the AutoCAD application with the volume results that have been carried out by the implementing contractor. For the result of excavation volume, the volume obtained by the author is smaller than the volume calculated by the implementing contractor, namely the volume comparison value is 614.65 m3 : 756.84 m3. For the volume of embankment, the volume obtained by the author is smaller than the volume calculated by the implementing contractor, namely the comparasion value is 1.189,3875 m3 : 1.439,76 m3.